Labour Income Segmentation by Migration Status, Gender, Race and Ethnicity in Uruguay - Márquez Scotti, Clara; Prieto Rosas, Victoria; Escoto Castillo, Ana (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2020)
The incorporation of recent immigrants into the Uruguayan labour market has shown a greater concentration in medium and high skilled occupations, with an important incidence of over-education. This process occurs in a labour market already segmented by different inequalities by occupational class, gender and race. This article examines whether the migration status introduces a new layer of segmentation. The results, based on estimations on labour income using the Continuous Household Survey for the period 2013-2017, point in this direction. The migration status and length of stay in Uruguay are intertwined with other layers of segmentation from the Uruguayan labour market, but in a variable manner throughout the distribution of income.
Keywords: south-south migration; immigration; race and ethnicity; income gap; Uruguay